Juridical Analysis of Alleged Violations of Article 14 of Law No. 5 of 1999 Related to Vertical Integration by Sany Group (Case Study: ICC Decision Number 18/ICC-L/2024) - Karin Brigitta; Ningrum Natasya Sirait; Robert Robert (Talenta Publisher, 2026)
The era of globalization has encouraged the influx of foreign investment into Indonesian industries, creating market structures that are vulnerable to anticompetitive practices by multinational corporations. The Sany Group case has become a significant precedent in the enforcement of Indonesian competition law. KPPU Decision Number 18/KPPU- L/2024 represents the first vertical integration case involving a foreign entity and resulted in a substantial administrative fine. This study examines the regulation of vertical integration under Indonesian competition law, the provisions governing dealer agreements with foreign business actors, and the juridical analysis of KPPU Decision Number 18/KPPU- L/2024 concerning the alleged violation of Article 14 of Law Number 5 of 1999 by Sany Group. This research employs a normative juridical method with a descriptive nature, utilizing statutory, conceptual, and case approaches. Data were collected through library research and analyzed qualitatively using a deductive reasoning framework. The findings indicate that, procedurally, the decision has fulfilled the elements required under Article 14. Substantively, however, the essence of Sany Group's violation lies in the abuse of economic dependence arising from asymmetrical bargaining power rather than merely vertical integration. The application of the extraterritoriality principle in this decision faces challenges because Law Number 5 of 1999 does not explicitly regulate the authority of the Business Competition Supervisory Commission (KPPU) in this regard. In practice, Sany Group's conduct more closely corresponds to the provisions of Article 25 concerning the abuse of a dominant position. The inability of Article 25 to adequately address this case stems from its quantitative approach based on market share thresholds. This study recommends revising the implementing guidelines of Article 25 to accommodate the concept of abuse of economic dependence and to clarify the extraterritorial authority of the KPPU.